THE IMPACT OF ARTIFICIAL INTELLIGENCE LITERACY ON LECTURERS' ACADEMIC PERFORMANCE AND WORKFLOW EFFICIENCY - Lely Novia; Noni, Nurdin (Lembaga Jurnal FKIP Universitas Bosowa, 2025)
This study evaluates the Artificial Intelligence (AI) literacy of university lecturers and examines its subsequent impact on their academic performance, covering teaching, research, and administrative tasks. With the rapid advancement of generative AI in education, AI literacy is crucial for maximizing efficiency and effectiveness. A mixed-methods approach, combining quantitative surveys and qualitative thematic interviews, was employed to measure understanding, needs, and perceived impact. The quantitative results reveal a high conceptual AI literacy (average score: 4.36) among lecturers, alongside strong optimism regarding AI’s transformative role in education (90.9% believing in major change). Quantitatively, AI significantly increases efficiency in lecture preparation and research productivity. Qualitatively, however, the implementation is challenged by critical issues of academic integrity and a lack of systemic readiness (regulations, infrastructure). The key finding is the dual role of AI: it acts as a valuable